AntiCOVID-19 Vaccines for Children - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
Emergency use authorization of the COVID-19 vaccine to prevent coronavirus disease 2019 is reported from the Medical Letter on Drugs and Therapeutics as well as from the contradictions presented by the drug producers to FDA and CDC for the messanger RNA vaccines to be approved or authorized. According to the knowledge of the first SARS and of the MERS, the children were not exposed to the civet and to the camels as the adults. The children are infected by the virus whitout suffering a serious illness, but they are an important source of infection. There is no COVID-19 emergency among children: there is no increase in mortality. The risks of hospitalization for COVID-19 in children are very low and often concern children with other pathologies. The children’s detection of the congenital defect of the MTHFR mutation makes them hypersensitive to the vaccine for thrombotic manifestations. One myocarditis every 10.000 inoculations for young people means risking much more for the vaccine than for the virus.